Differentiation of Pythium spp. from vegetable crops with molecular markers and sensitivity to azoxystrobin and mefenoxam. Issue 2 (28th August 2018) - Matić, Slavica; Gilardi, Giovanna; Gisi, Ulrich; Gullino, Maria Lodovica; Garibaldi, Angelo
Abstract: BACKGROUND: Pythium species attack various vegetable crops causing seed, stem and root rot, and 'damping‐off' after germination. Pythium diseases are prevalently controlled by two classes of fungicides, QoIs with azoxystrobin and phenlyamides with mefenoxam as representatives. The present study aimed to test the sensitivity of six Pythium species from different vegetable crops to azoxystrobin and mefenoxam and differentiating species based on ITS, cytochrome b and RNA polymerase I gene sequences. RESULTS: The inter‐ and intra‐species sensitivity to azoxystrobin was found to be stable, with the exception of one Pythium paroecandrum isolate, which showed reduced sensitivity and two cytochrome b amino acid changes. For mefenoxam, the inter‐species sensitivity was quite variable and many resistant isolates were found in all six Pythium species, but no RNA polymerase I amino acid changes were observed in them. ITS and cytochrome b phylogenetic analyses permitted a clear separation of Pythium species corresponding to globose‐ and filamentous‐sporangia clusters. CONCLUSION: The results document the necessity of well‐defined chemical control strategies adapted to different Pythium species. Since the intrinsic activity of azoxystrobin among species was stable and no resistant isolates were found, it may be applied without species differentiation, provided it is used preventatively to also control highly aggressive isolates. For a reliable use of mefenoxam, precise identification and sensitivity tests of Pythium species are crucial because its intrinsic activity is variable and resistant isolates may exist. Appropriate mixtures and/or alternation of products may help to further delay resistance development. © 2018 Society of Chemical Industry Abstract : This study indicates stable intrinsic activity of azoxystrobin, which may be applied without differentiation of Pythium species, while mefenoxam requires precise species identification before treatment due to its variable intrinsic activity.